Customer Satisfaction and Challenges in Online Food Delivery: A Study in Surigao del Sur - Orcullo, Kent G.; Grefalde, James Q. (International Journal of Scientific Research and Management (IJSRM), 2025)
With the rapid growth of online food delivery services, understanding customer satisfaction has become increasingly important for ensuring service quality and competitiveness. This study aimed to assess the level of customer satisfaction and identify the common challenges encountered by users of online food delivery platforms. Using a quantitative-descriptive research design, the study surveyed 390 respondents through a structured questionnaire. The participants were mostly young adults aged 18–25, predominantly female, and largely composed of single individuals with modest monthly incomes ranging from ₱10,000 to ₱29,999. Results revealed a generally high level of satisfaction across core service areas such as delivery accuracy, order fulfillment, and customer service. However, challenges like limited delivery range, lack of food variety, and occasional order errors were observed, though not perceived as highly serious. These findings suggest that while current delivery services meet customer expectations, addressing these areas could further enhance user experience and loyalty. The study offers practical insights for improving service delivery and highlights the need for more adaptive and responsive strategies in the online food service sector.